Identifying the Transcriptome Signatures of Calcium Channel Blockers in Human Induced Pluripotent Stem Cell-Derived Cardiomyocytes - Lam, Chi Keung (Circ Res, 2019)
RATIONALE: Calcium channel blockers (CCBs) are an important class of drugs in managing cardiovascular diseases. Patients usually rely on these medications for the remainder of their lives after diagnosis. Although the acute pharmacological actions of CCBs in the hearts are well-defined, little is known about the drug-specific effects on human cardiomyocyte transcriptomes and physiological alterations after long-term exposure. OBJECTIVE: This study aimed to simulate chronic CCB treatment and to examine both the functional and transcriptomic changes in human cardiomyocytes. METHODS AND RESULTS: We differentiated cardiomyocytes and generated engineered heart tissues from three human induced pluripotent stem cell (iPSC) lines and exposed them to four different CCBs—nifedipine, amlodipine, diltiazem, and verapamil—at their physiological serum concentrations for two weeks. Without inducing cell death and damage to myofilament structure, CCBs elicited line-specific inhibition on calcium kinetics and contractility. While all four CCBs exerted similar inhibition on calcium kinetics, verapamil applied the strongest inhibition on cardiomyocyte contractile function. By profiling cardiomyocyte transcriptome after CCB treatment, we identified little overlap in their transcriptome signatures. Verapamil is the only inhibitor that reduced the expression of contraction-related genes, such as myosin heavy chain and troponin I, consistent with its depressive effects on contractile function. The reduction of these contraction related genes may also explain the responsiveness of HCM patients to verapamil in managing left ventricular outflow tract obstruction. CONCLUSIONS: This is the first study to identify the transcriptome signatures of different CCBs in human cardiomyocytes. The distinct gene expression patterns suggest that although the four inhibitors act on the same target, they may have distinct effects on normal cardiac cell physiology.